Wideband helicity dependent spoof surface plasmon polaritons coupling metasurface based on dispersion design - Dong, Guoxiang (Sci Rep, 2016)
The surface plasmon polaritons (SPPs) have many potential application due to their local field enhancement and sub-wavelength characteristics. Recently, the gradient metasurface is introduced to couple the spoof SPPs in microwave frequency band. One of the most important issue which should be solved is the narrowband of spoof SPPs coupling on the gradient metasurface. Here, the metasurface is proposed to achieve the wideband helicity dependent directional spoof SPPs coupling for circular polarized light. Our research show that the coupling frequency of spoof SPPs on the gradient metasurface is determined by the dispersion of the metasurface, so the coupling frequency can be controlled by dispersion design. The careful design of each cell geometric parameters has provided many appropriate dispersion relations possessed by just one metasurface. The wave vector matching between the propagating wave and the spoof SPPs has been achieved at several frequencies for certain wave vector provided by the metasurface, which leads to wideband spoof SPPs coupling. This work has shown that wideband helicity dependent directional spoof SPPs coupling has been achieved with a high efficiency. Hence, the proposed wideband spoof SPPs coupling presents the improvement in practice applications.